2004
DOI: 10.1021/bi0491651
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of mRNA 5‘ Cap Binding by Eukaryotic Translation Initiation Factor eIF4E

Abstract: Translation of mRNA in eukaryotes begins with specific recognition of the 5' cap structure by the highly conserved protein, eIF4E. The thermodynamics of eIF4E interaction with nine chemical cap analogues has been studied by means of emission spectroscopy. High-sensitivity measurements of intrinsic protein fluorescence quenching upon cap binding provided equilibrium association constants in the temperature range of 279 to 314 K. A van't Hoff analysis yielded the negative binding enthalpies for the entire cap an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 74 publications
(122 reference statements)
6
55
0
Order By: Relevance
“…This model suggests that intrinsic and specific conformational flexibility of the schistosome eIF4E plays the crucial role for m 2,2,7 G cap binding. Steric hindrance of the cap due to the additional two methyl groups at the N 2 position of the m 2,2,7 G cap has been suggested previously to likely be important in the reduced affinity of mammalian eIF4E in binding m 2,2,7 G cap (9,21). Previous mutagenesis studies for C. elegans eIF4E-5, a form of eIF4E that can bind both types of caps, showed that two residue changes (N64Y/V65L) (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This model suggests that intrinsic and specific conformational flexibility of the schistosome eIF4E plays the crucial role for m 2,2,7 G cap binding. Steric hindrance of the cap due to the additional two methyl groups at the N 2 position of the m 2,2,7 G cap has been suggested previously to likely be important in the reduced affinity of mammalian eIF4E in binding m 2,2,7 G cap (9,21). Previous mutagenesis studies for C. elegans eIF4E-5, a form of eIF4E that can bind both types of caps, showed that two residue changes (N64Y/V65L) (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Fluorescence intensity was corrected for the inner filter effect, and the emission of the free cap analogs was explicitly included in the numerical analysis. A theoretical curve for the fluorescence intensity as a function of the total ligand concentration was fitted to the experimental data points by means of non-linear, least squares method using Prism 3.02 (GraphPad Software) as described previously (9,30,41).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations